РОЗПОДІЛЕННЯ ЕЛЕКТРОСТАТИЧНОГО ПОЛЯ У НЕЕКРАНОВАНИХ СИЛОВИХ КАБЕЛЯХ З РІЗНОЮ КОНФІГУРАЦІЄЮ СТРУМОПРОВІДНИХ ЖИЛ - Безпрозванних, Г.В.; Гонтар, Ю.Г.; Пушкар, І.А. (Інститут електродинаміки НАН України, Київ, 2025)
Introduction. Nuclear energy is an undeniable component of green energy and makes a significant contribution to achieving sustainable development goals and increasing the country's energy security. It is a reliable and predictable source of electricity for up to 60 years with an average cost of energy produced of 0.4 euros/kWh. Problem. Nuclear power plants consist of different zones that differ in ambient temperature, radiation level, and requirements for testing resistance to accidents. Cables for nuclear power plants are constantly exposed to difficult conditions throughout their entire service life and must provide reliable power supply, meet environmental safety and economic efficiency requirements. The introduction of modern innovative polymer compositions requires a comprehensive analysis of the influence of electrical insulation on the electrical parameters of cables of various designs at the stage of their design and production to ensure a high level of operational functionality at nuclear power plants. The purpose of the work is to analyze the distribution of the electrostatic field around insulated conductive cores of various configurations with the determination of their electrical capacitance in unshielded power cables of local power supply systems of the turbine compartment of nuclear power plants. The methodology is based on determining the electric charge density by the secondary source method based on the Fredholm integral equations of the first and second kind in models of unshielded power cables with sector and round conductive cores. Scientific novelty. The distribution of the plane-parallel electrostatic field in unshielded power cables has been determined depending on the scheme of applying an electric potential (zero and non-zero, equal to 1000 V) to conductive cores of various configurations.  It has been proven that in a power cable with cores of a uniform configuration, under the condition of creating a dipole spatial distribution of the electrostatic field, the electric capacitances between the cores have the largest values. The correctness of the obtained theoretical provisions has been experimentally confirmed, which is confirmed by the coincidence of the calculated values ​​of the electric capacitance with the experimental values ​​with a difference of 8.5%. Practical significance. The electric field strength on the surface of the electrical insulation of the cores has been determined depending on the inspection scheme when applying the working and increased test voltage. It is proposed to fill the interphase space with a dielectric material with a dielectric permittivity ε1=2.0 to reduce the electrostatic field strength by 2 times in the air gaps at the technological stage of cable manufacturing. The presented methodology for determining the spatial distribution of the electrostatic field around insulated conductive cores of various configurations can be used to estimate the values ​​of the electrical capacitance of insulating gaps as reference for controlling cables at the technological stage of manufacturing during acceptance tests and in operational conditions. References 27, figures. 7.